STRATEGI KOMUNIKASI PEMASARAN PT. BORWITA CITRA PRIMA DALAM MENARIK MINAT TOKO KELONTONG DI SURABAYA - YOGI, SUPRAYOGI PRAKARYO (Journal Communication Specialist, 2022)
Borwita Group is an independent distributor company focused in eastern Indonesia. Founded in 1976 by Mr. Hady Karyono, Borwita started the distribution of consumer products. Since 2014. Borwita has expanded its business to start a Logistics Services unit. Leveraging its strong network and infrastructure, Borwita Logistics provides logistics services for P&G, Frisian Flag Indonesia, Pocari Sweat, Nutrifood, Big Cola, SC Johnson, and many more. In the overall marketing or marketing mission as well as determining the success of Borwita Group marketing, marketing communication is an important aspect, so the main problem of this research is focused on how the marketing communication strategy of PT Borwita Citra Prima in attracting the interest of grocery stores in the city of Surabaya based on the theory of SOSTAC using qualitative research methods descriptive, the process of searching for data through interviews with key informants, namely Mr. Yulianto as SPV Marketing with the aim of knowing the marketing communication strategy of PT Borwita Citra Prima in attracting the interest of Grocery Stores in the City of Surabaya. As a result, the implementation of a marketing communication strategy to find consumers in the city of Surabaya includes surveys and regional mapping, division of regional sales teams, recording store names, owner names, store locations, and what orders the grocery store wants.PT Borwita Citra Prima's marketing communication strategy with SOSTAC theory has proven to be effective with the achievement of marketing targets, this is also influenced by human resource management due to self-evaluation and development through the Training Cycle. Borwita Group adalah perusahaan distributor independen yang terfokus di Indonesia bagian timur. Didirikan pada tahun 1976 oleh Bapak Hady Karyono, Borwita memulai distribusi produk konsumtif. Sejak tahun 2014. Borwita telah memperluas bisnisnya untuk memulai unit Layanan Logistik. Memanfaatkan jaringan dan infrastrukturnya yang kuat Borwita Logistics melayani layanan logistik untuk P&G, Frisian Flag Indonesia, Pocari Sweat, Nutrifood, Big Cola, SC Johnson, dan banyak lagi.  Dalam keseluruhan misi marketing atau pemasaran serta penentu suksesnya pemasaran Borwita Group, komunikasi pemasaran adalah aspek penting, sehingga pokok permasalahan Penelitian ini terfokus pada bagaimana strategi komunikasi pemasaran PT Borwita Citra Prima dalam menarik minat toko kelontong di Kota Surabaya dengan landasan teori SOSTAC menggunakan metode penelitian kualitatif deskriptif, proses pencarian data melalui wawancara dengan key informan yakni Bapak Yulianto selaku SPV Marketing dengan tujuan mengetahui strategi komunikasi pemasaran PT Borwita Citra Prima dalam menarik minat Toko Kelontong di Kota Surabaya. Hasilnya, pelaksanaan strategi komunikasi pemasaran untuk mencari konsumen di Kota Surabaya meliputi survey dan pemetaan wilayah, pembagian tim sales perwilayah, mendata nama toko, nama pemilik, lokasi toko, dan pesanan apa yang diinginkan oleh toko kelontongnya. Strategi komunikasi pemasaran PT Borwita Citra Prima dengan teori SOSTAC terbukti efektif dengan tercapainya target pemasaran, hal ini dipengaruhi juga pengelolaan sumber daya manusia karena adanya evaluasi dan pengembangan diri melalui Training Cycle.